MENINGKATKAN KEMAMPUAN AFEKTIF SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE PADA PELAJARAN PKN KELAS VI SDN 104204 SAMBIREJO TIMUR - Erniwaty Batubara (Universitas Negeri Medan, 2018)
Abstract: Improving Student's Affective Ability Using Value Clarification Technique Learning Model On PKN Class VI Study SDN 104204 Sambirejo Timur. The formulation of the problem in this research is whether by using the learning model Value clarification technique can improve students' affective ability on the subject matter of Joint Decision class VIb SDN 104204 Sambirejo East?